2019
DOI: 10.1111/jgs.16129
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Matters More Than Experience for Advance Care Planning Knowledge Among Older Adults

Abstract: BACKGROUND Advance care planning (ACP) engagement is low among vulnerable populations, including those with limited health literacy (LHL). Limited knowledge about ACP may be a modifiable mediator of the relationship between LHL and ACP. Our goal was to determine whether health literacy is associated with ACP knowledge. DESIGN Cross‐sectional design. SETTING A public health delivery system and Veterans Affairs Medical Center in San Francisco, CA. PARTICIPANTS English‐ and Spanish‐speaking patients (N = 1400). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 34 publications
(75 reference statements)
4
44
0
Order By: Relevance
“…We also found that higher health literacy was associated with preference for supportive kidney care, which reinforces the importance of clear communication and dialogue between clinicians and patients to better assist them in navigating their health decisions [46]. Health literacy has been associated with advance care planningan important consideration for older patients with advanced CKD [47][48][49]. Further investigation is warranted to ascertain whether the addition of an educational supportive kidney care video decision aid in clinical practice can influence patient-centered outcomes, including advance care planning and treatment decision-making.…”
Section: Discussionsupporting
confidence: 61%
“…We also found that higher health literacy was associated with preference for supportive kidney care, which reinforces the importance of clear communication and dialogue between clinicians and patients to better assist them in navigating their health decisions [46]. Health literacy has been associated with advance care planningan important consideration for older patients with advanced CKD [47][48][49]. Further investigation is warranted to ascertain whether the addition of an educational supportive kidney care video decision aid in clinical practice can influence patient-centered outcomes, including advance care planning and treatment decision-making.…”
Section: Discussionsupporting
confidence: 61%
“…20 Advance care directives written in plain language improve comprehension, acceptability, and usefulness for consumers. 21 Prospective participants' views on research documents and the impacts of plain language documents on research participation have been understudied. 22 These are vital areas for future research on ARDs.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a pluralism of values and beliefs within a multicultural society, including the influence of cultural values from countries of origin ( Bito et al, 2007 ). Importantly however, these ethnic disparities in ACP uptake are sensitive to sociodemographic and psychosocial factors, including education level and personal control ( Inoue, 2016 ), socioeconomic status ( Koss & Baker, 2018 ), health literacy ( Nouri et al, 2019 ), religiosity, and trust in health care providers ( Johnson et al, 2008 ). The disparity between White American and African American people in terms of ACP uptake has also reduced in recent years ( Koss & Baker, 2017 ).…”
mentioning
confidence: 99%